Ambient Intelligence At-Home Laboratory for Human Everyday Life - Korzun, Dmitry G; Borodin, Alexander V; Zavyalova, Yulia V; Meigal, Alexander Yu; Gerasimova-Meigal, Liudmila I (International journal of embedded and real-time communication systems, 2019)
The relation of artificial intelligence (AI) and human intelligence (HI) still needs better understanding. In this article, the authors develop the fourth brain concept where AI is considered as a specific form of HI evolution. The concept development considers evolutionary and ontogenetic insights on intelligence. The forth brain can be implemented using ambient intelligence (AMI) environments that surround humans in everyday life. AMI environment allows scaffolding and other assistance information services to compensate for the HI function decay. This article proposes an at-home laboratory (AHL) design where an AMI environment is deployed at home and using everyday devices. In this setting, AHL provides a functionally equivalent alternative to the professional healthcare laboratory, though less accurate and advanced in regard to data measurements and the assistance information value.